Blocking Ocular Sympathetic Activity Inhibits Choroidal Neovascularization - Martinez-Camarillo, Juan Carlos; Spee, Christine K.; Trujillo-Sanchez, Gloria Paulina; Rodriguez, Anthony; Hinton, David R.; Giarola, Alessandra; Pikov, Victor; Sridhar, Arun; Humayun, Mark S.; Weitz, Andrew C. (Frontiers in Neuroscience, 2022)
Purpose To investigate how modulating ocular sympathetic activity affects progression of choroidal neovascularization (CNV), a hallmark feature of wet age-related macular degeneration (AMD). Methods In the first of two studies, Brown Norway rats underwent laser-induced CNV and were assigned to one of the following groups: daily eye drops of artificial tears (n=10; control group); daily eye drops of the β-adrenoreceptor agonist isoproterenol (n=10); daily eye drops of the β-adrenoreceptor antagonist propranolol (n=10); sympathetic internal carotid nerve (ICN) transection 6 weeks prior to laser-induced CNV (n=10). In the second study, rats underwent laser-induced CNV followed by ICN transection at different time points: immediately after the laser injury (n=6), 7 days after the laser injury (n=6), and sham surgery 7 days after the laser injury (n=6; control group). All animals were euthanized 14 days after laser application. CNV development was quantified with fluorescein angiography and optical coherence tomography (in vivo), as well as lesion volume analysis using 3D confocal reconstruction (postmortem). Angiogenic growth factor protein levels in the choroid were measured with ELISA. Results In the first study, blocking ocular sympathetic activity through pharmacological or surgical manipulation led to a 75% or 70% reduction in CNV lesion volume versus the control group, respectively (P<0.001). Stimulating ocular sympathetic activity with isoproterenol also led to a reduction in lesion volume, but only by 27% versus controls (P<0.05). VEGF protein levels in the choroid were elevated in the three treatment groups (P<0.01). In the second study, fluorescein angiography and CNV lesion volume analysis indicated that surgically removing the ocular sympathetic supply inhibited progression of laser-induced CNV, regardless of whether ICN transection was performed on the same day or 7 days after the laser injury. Conclusions Surgical and pharmacological block of ocular sympathetic activity can inhibit progression of CNV in a rat model. Therefore, electrical block of ICN activity could be a potential bioelectronic medicine strategy for treating wet AMD.